PENGETAHUAN PESERTA PROGRAM PENDIDIKAN DOKTER SPESIALIS NEUROLOGI INDONESIA TENTANG SEMIOLOGI BANGKITAN EPILEPSI - Suryani Gunadharma; Yovita Stevina; Anam Ong; Siti Aminah; Lisda Amalia; Uni Gamayani (NEURONA, 2020)
Introduction: Seizure semiology is an effective method for syndrome diagnosis, especially when electroencephalogram (EEG) and brain magnetic resonance imaging (MRI) cannot provide sufficient information. Diagnosis of clinical epilepsy based on semiology required a comprehensive knowledge especially for neurology residentsandidate of neurology specialist. Aim: To assess the knowledge of Indonesian neurology resident about seizure semiology. Methods: This observational descriptive study was conducted from 4 choosen university in Indonesia from February to September 2019. Participants were neurology residents from 1st semester to 8th semester. Participants were asked to fill in that quetionnaire consist of 6 questions about the teaching of seizure semiology in their university. Five ictal videos were presented to be analyzed for semiology, lateralization, and localization. These videos were chosen by 3 epilepsy consultants from different universities. Results: The participants consist of 135 residents, 16 in the 1st semester, 21 in the 2nd, 18 in the 3rd, 14 in the 4th, 14 in the 5th, 15 in the 6th, 19 in the 7th, 18 in the 8th semester. Video semiology were already lectured from the 3rd semester in 66.7%-83%. Only 30.3% of semiology features from 5 videos can be recognized by the participants, semiology knowledge was improved from 2nd semester. An average of 55.6% participants could answer lateralization and 52% localization. Discussion: Neurology resident knowledge about seizure semiology is still insufficient, improvement and uniformity in teaching methodology of semiology is needed. Keywords: Indonesian neurology resident, knowledge, seizure semiology